INTERTEXTUAL ANALYSIS OF FOLKLORIC MOTIFS IN THE POETIC WORLD OF SERGEI YESENIN (Eureka Journal of Education & Learning Technologies, 2026)
The article presents an intertextual analysis of folkloric motifs in the poetry of S.A. Yesenin. It examines both explicit and latent forms of folklorism manifested through allusions, reminiscences, stylization, and symbolism. Special attention is given to the interaction between the folk and authorial poetic systems, as well as to the function of folkloric elements in the creation of artistic imagery and the representation of a cosmogonic concept. It is emphasized that S.A. Yesenin’s appeal to folklore is creative in nature, forming a dialogue between tradition and the author’s vision rather than a simple borrowing.
Keywords: S.A. Yesenin, folklorism, intertextuality, allusion, reminiscence, stylization, symbol, poetics, ritual poetry, literary analysis.